Journeys to health : middle-class Mozambican women assess healthcare service delivery in Mozambique and South Africa - Chichava, Marina (Social Anthropology, 2014)
My thesis explores how Mozambican middle-class women perceive official local healthcare services in both their public and private dimensions, within their country, and why they sometimes travel abroad to South Africa in search of healthcare across a range of gynaecological services, ranging from basic procedures to more complex requirements. I trace the stories of fifteen women to convey their experiences and opinions of the Mozambican health system. I show the women negotiating their way through barriers and limitations within this system, in ways that point out its inadequacies and inefficiency. I investigate how searching for 'quality' healthcare, often abroad, is intertwined with middle-class women's crafting of identities that aspire to a certain demonstration of 'modernity' in which social status is claimed.